Orange Shirt Day Healing Event (2021-09-30) - University of Minnesota Duluth. American Indian Learning Resource Center (My University, 2021)
Let's remember our relatives and survivors of the residential boarding schools
Thursday, September 30th; 2-6 pm; AILRC; 315 Kirby Plaza; Hot Tea, Coffee & Snacks; Reflection Activities 2 - 4:30 pm; Talking Circle 4:30 pm
Keywords: Posters; University of Minnesota Duluth; American Indian Learning Resource Center; Indigenous Student Organization; Center for Regional and Tribal Child Welfare Studies; Student organizations